Rynek praw majątkowych do świadectw pochodzenia energii ze źródeł odnawialnych w Polsce - Graczyk, Alicja (Property Market of Energy Origin Certificates from Renewable Energy Sources in Poland, 2009)
The main goal of the article is an approximation of functioning of the property market principles of energy origin certificates from renewable energy sources. The paper also analyzes the functioning of this market and estimates market failure. The property market of energy origin certificates is a part of renewable energy sources (RES) market and an essential element of the applied system of support. Both the property market of energy origin certificates and the complex system of support are estimated as non pure market mechanisms. RES Market is in considerable part regulated. The price of electric energy is established by authorities as well as the minimum quantity of purchased certificates of origin of energy from a renewable source. From the another point of view, on the property market of energy origin certificates, which reflects the real value of green energy, buyers and sellers can freely define quantity of sold and bought goods and then the market mechanism shapes the price (the feature of perfectly competitive market, pure market solution). The stock exchange assures all participants equal access to the market and perfect market information. RES support mechanisms are relating to the protection of energy sources solutions. The government plays a considerable part in functioning and the creation of this market. Therefore presented market solutions are not a pure market solutions indeed
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 201-211